Internet of Things-based Gas Leak Detection with Alerts Via SMS and Blynk App - Yusuf, Revy Muhammad; W, Ari Purno Wahyu (Politeknik Ganesha Medan, 2022)
Gas cylinders are one of the needs that humans use every day. The use of gas cylinders is often used for cooking, both for household needs and industrial needs. Gas leaks are a big problem that can give rise to explosions and fires due to combustible gas. Explosions and fires that occur as a result of this gas leak can cause a lot of losses. This study aims to build an Internet of Things-based gas leak detection tool using NodeMCU ESP8266 as a microcontroller that functions as a brain to execute commands that have been made. Blynk App and SMS to provide information to users in case of gas leaks detected by MQ-6 sensors. This tool will detect gas leaks that occur by receiving data from the MQ-6 sensor which is then processed by NodeMCU ESP8266. If a gas leak is detected, the buzzer will sound and the tool will give an alert by popping up a notification on the Blynk application with an internet connection and sending an alert via SMS so that the alert can be sent even in the absence of an internet connection. With this tool, users can find out earlier if there is a gas leak by getting a notification on the Blynk application and receiving a gas leak SMS, to avoid explosions and minimize damage and losses caused by gas leaks.